Ketidakefektifan Penggunaan Kondom Pada Pasangan Usia Subur - Parinussa, Nenny (REAL in Nursing Journal, 2020)
ABSTRACTFertile Age Couple (PUS) acceptors of condom contraception in Maluku in 2018 in the 30-49 age category is 0.9 percent. The working area of the Ambon Tulehu Community Health Center is 1,877 PUS, 1,467 active family planning participants and 2 condom family planning acceptors. The data shows the lack of male participation in contraceptive use, including condoms. This study aims to get a picture of the ineffectiveness of condom use in PUS men in the working area of the Ambon Tulehu Community Health Center. The research design is qualitative using a phenomenological approach. Participants in this study were 8 PUS men who had used a condom and then no longer / switched to other methods of contraception. The results of the study were the reasons participants used condoms to avoid getting pregnant, preventing illness, trial and error, inexpensive. The reason participants stopped using condoms was because they were uncomfortable, bothered to use it, embarrassed, reduced sexual pleasure, caused pain for the wife, there were obstacles and their effectiveness was not guaranteed. Motivational research suggestions for prospective acceptors are very important to use condoms as an alternative method of contraception. Keywords: Ineffectiveness of Condoms1, Fertile Age Couples2